2009
DOI: 10.1017/s0021859609008600
|View full text |Cite
|
Sign up to set email alerts
|

Cold hardiness of olive (Olea europaeaL.) cultivars in cold-acclimated and non-acclimated stages: seasonal alteration of soluble sugars and phospholipids

Abstract: SUMMARYIn many plant species, several physiological and biochemical changes occur during low-temperature-induced cold acclimation. A previous study with olive cultivars (Cansevet al.2009) demonstrated a correlation between the level of accumulation of certain leaf proteins besides antioxidative enzyme activities and cold hardiness of the cultivars. The present paper analysed soluble sugar (SS) and phospholipid (PL) contents of cold-acclimated (CA) and non-acclimated (NA) leaf tissues in order to explain the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Furthermore, changes in phospholipids composition in plasmatic membrane contribute to tissue rigidity during cold acclimatation (Griffith & Brown ; Larcher ; Gulen et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, changes in phospholipids composition in plasmatic membrane contribute to tissue rigidity during cold acclimatation (Griffith & Brown ; Larcher ; Gulen et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Enhanced pectin synthesis has been observed in the cell walls of other species during cold acclimation (Kubacka-Zebalska & Kacperska 1999;Baldwin et al 2014) which contributes to lower porosity of the cell wall and possibly to increase ε. Furthermore, changes in phospholipids composition in plasmatic membrane contribute to tissue rigidity during cold acclimatation (Griffith & Brown 1982;Larcher 1982;Gulen et al 2009).…”
Section: Freezing Cell Injury and Supercooling In Acclimated And Non-mentioning
confidence: 99%
“…The Pn, Gs, and Tr were reduced, but the Ci was increased after the application of DPI or DMTU, hinting a possibility that H 2 O 2 is involved in wounding induced photoinhibition. Freezing responses are associated with the changes in antioxidant system ( Gulen et al, 2009 ; Zhou et al, 2012 ). Consistent with earlier studies, we found that the activities of antioxidant enzymes, such as SOD, CAT, APX, and GR, were increased after wounding and freezing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that there is a correlation between some physiological and biochemical characteristics such as stomatal density (Roselli et al 1989), stomatal size (Roselli and Venora 1990), phenolic compounds (Roselli et al 1992), differential thermal analysis (Martin et al 1993), ionic leakage Azzarello et al 2009), fractal analysis (Azzarello et al 2009), impedance spectroscopy (Azzarello et al 2009), soluble sugars Bartolozzi et al 2001;Gulen et al 2009) and total soluble proteins (Eris et al 2007;Cansev et al 2009) with frost-tolerant in olive genotypes. Currently, interesting results to quantify cold tolerance have come from the study of some antioxidant enzymes (Solecka and Kacperska 2003;Cansev et al 2009;Ortega-García and Peragón 2009).…”
Section: Introductionmentioning
confidence: 93%